Analysis of Student Errors in Solving Equations and Inequalities Problems in Algebra and Trigonometry Based on Newman Procedure - Miftahul Jannah; Anekke Pesik; Selfie Kumesan; Ermita Ermita; Nurdin Rahim (CV. Pusdikra Mitra Jaya, 2024)
The purpose of this study is to examine how students make mistakes when attempting to solve equality and inequality problems in trigonometry and algebra using the Newman method. A qualitative descriptive research methodology is employed in this study. Students enrolled in Manado State University's 2023–2024 Mathematics Education Study Program during their first semester served as the research subjects. Test and interview techniques are used in data collection. Three steps made up the data analysis in this study: reduction, data display, and data verification. Data analysis utilizing the Newman approach yielded the following conclusions: 5.6% encoding errors, 4.8% reading errors, 12% comprehension errors, 8.4% transformation errors, and 18.8% process skill errors were made when solving equation and inequality problems. The inability of pupils to comprehend the concept of the subject being explained, their lack of willingness to study, and their carelessness when reading and completing questions are the causes contributing to these blunders.